A Comparative Analysis of Compressive and Flexural Strength in Concrete with Partial Cement Replacement using Waste Glass Powder - Hedayat Ullah Safi; Mohammad Mukhlis Behsoodi; Mohammad Naseer Sharifi (Indonesian Journal of Material Research, 2024)
This experimental inquiry delves into the evaluation of compressive and flexural strengths in concrete through the utilization of waste glass powder as a partial substitute for cement. Compressive strength is a key metric, indicating the concrete’s ability to effectively support structural axial loads, while flexural strength signifies its capacity to withstand deformation under bending, specifically the maximum tensile stress it can endure without fracturing when subjected to a bending moment. Certain pozzolanic materials have demonstrated the ability to enhance the mechanical strength of concrete when used as a cement replacement, and waste glass powder is among them. To address this, the experimental investigation included the substitution of cement with glass powder at different proportions (0%, 10%, 15%, 17.5%, and 20%) in both cubic and prismatic samples. Compressive strength and flexural strength tests were made following the curing of the samples for 7, 14, and 28 days. The findings indicated that the 17.5% cement replacement level exhibited a 6.07% over-strength for compressive strength and a 6.85% over-strength for flexural strength on the 28th day. However, the 15% replacement showed superior strength compared to a 10% replacement, and the 10% replacement was stronger than a 0% cement replacement. Notably, the 20% cement replacement displayed negative over-strength percentages, specifically -2.42% in compressive strength and -1.42% in flexural strength on the 28th day. This deviation raises concerns about its suitability for use in concrete applications, signifying that a 20% replacement may not be recommended.